2017
DOI: 10.1155/2017/6927416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanotube Geometry on the Strength and Dispersion of CNT-Cement Composites

Abstract: This study investigated the effect of multiwalled carbon nanotubes' geometry on the dispersion and strength of cement composites. Mixes with CNTs contents ranging from 0.03 to 0.25% were prepared and tested using CNTs' diameters of 10-20, 20-30, and 30-50 nm and lengths of 0.5-2 and 10-30 m. The samples' microstructures were then examined using a scanning electron microscope. After that, Response Surface Methodologies techniques were implemented to determine the strength functions' response to the aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This improvement resulted in a flexural strength increase of about 100% compared to a plain cement paste. Also, the researchers conducted a set of experiments that investigated the effect of several parameters on the dispersion of CNTs in cement paste, such as CNT weight fractions, diameters, and lengths [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This improvement resulted in a flexural strength increase of about 100% compared to a plain cement paste. Also, the researchers conducted a set of experiments that investigated the effect of several parameters on the dispersion of CNTs in cement paste, such as CNT weight fractions, diameters, and lengths [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of CNTs is also considered to be an influential factor in terms of dispersion and mechanical performance. Mohsen et al [60] reported that a cementitious composite containing CNTs with the lowest diameter and a high aspect ratio achieved higher mechanical strength when compared to CNTs with a medium or larger diameter (Figure 18). Besides, a cementitious composite containing longer CNTs achieved a slightly higher flexural strength.…”
Section: Mechanical Properties Of Cementitious Composites Incorporatimentioning
confidence: 99%
“…Owing to their excellent physical and mechanical properties, carbon nanotubes (CNTs) are favorable nano-fillers for cementitious composites [1,2] and has received extensive attention from researchers and engineers [3,4]. For example, compressive, flexural, tensile, and splitting strengths of cementitious composites can be increased by 50 %, 269 %, 19 %, and 86 %, respectively [3,5,6], due to the addition of CNTs. Meanwhile, the incorporation of CNTs endows cementitious composites with excellent piezoresistive properties [7,8], electromagnetic interference shielding properties [9] and damping performances [10,11].…”
Section: Introductionmentioning
confidence: 99%